Hierarchical broad learning system for hyperspectral image classification. Issue 2 (24th November 2021) - Xiao, Guangrun; Wei, Yantao; Yao, Huang; Deng, Wei; Xu, Jiazhen; Pan, Donghui
Abstract: A new spectral‐spatial hyperspectral image (HSI) classification method called hierarchical broad learning system (HBLS) has been proposed in this paper. Specifically, it combines wavelet, broad learning system (BLS) and Gabor filters into a hierarchical structure. First of all, wavelet is used to reduce the observation noise of HSIs. Then BLS is adopted to acquire a set of pixelwise probability maps from the input data, and Gabor filters are used to explore spatial information by refining these probability maps. These two operations (BLS and Gabor filtering) are alternated to form a hierarchical architecture. And the discriminative spectral‐spatial features can be extracted at each layer of the hierarchical architecture. Finally, the spectral‐spatial features are fed into the standard BLS for classification. Experimental results on three widely used HSIs reveal that HBLS outperforms some state‐of‐the‐art methods in terms of classification accuracy and sample complexity.